2020
DOI: 10.3390/cancers12102990
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities and Survival Characteristics in Non-Pancreatic Gastrointestinal Tract Neuroendocrine Tumors

Abstract: Background: We studied the effect of race and ethnicity on disease characteristics and survival in gastrointestinal neuroendocrine tumors. Methods: The Surveillance, Epidemiology, and End Results database was used to select patients with non-pancreatic gastrointestinal neuroendocrine tumors diagnosed between 2004 and 2015. Trends in survival were evaluated among three groups: Hispanic, non-Hispanic White, and non-Hispanic Black. Kaplan–Meier and Cox regression methods were performed to calculate overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Notably, Hispanic patients demonstrated better overall survival rates, whereas non-Hispanic Black patients showed improved cause-specific survival rates when compared to their non-Hispanic White counterparts. These findings were confirmed in multivariable analysis, indicating that race and ethnicity serve as independent prognostic factors in patients with gastrointestinal NETs [27].…”
Section: Discussionmentioning
confidence: 59%
“…Notably, Hispanic patients demonstrated better overall survival rates, whereas non-Hispanic Black patients showed improved cause-specific survival rates when compared to their non-Hispanic White counterparts. These findings were confirmed in multivariable analysis, indicating that race and ethnicity serve as independent prognostic factors in patients with gastrointestinal NETs [27].…”
Section: Discussionmentioning
confidence: 59%
“… 3 4 The cause of this difference, especially regarding the incidence of small intestinal NETs, is unknown. One study from the United States reported significant racial/ethnic disparities in the incidence of gastrointestinal NETs, 20 although Asians were not included in that study.…”
Section: Discussionmentioning
confidence: 99%